MEMBANGUN CIVIC ENGAGEMENT MELALUI MODEL SERVICE LEARNING UNTUK MEMPERKUAT KARAKTER WARGA NEGARA - Eli Karliani (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2014)
Rapid social changes as the result of knowledge and technology progress have been shifted good values to the new ones which are scraping the good values. Citizenship education should be the education of a thinking process. It also should be the education of values, characters, and attitudes. It is due to the fact that education of values, characters, and attitudes does support the building of a nation’s characters. In achieving the goal of education of values, characters, and attitudes, habituation efforts are needed. It can be done through internalization and application of civic knowledge, civic values, and civic skills. Students not only have to learn from classes, but also apply those three competence in problem solving in their real lives. Those three competence will be achieved if every individuals have civic engagement in their community life. Service learning method is considered as a good way to internalize values and applying the competence of the students. Furthermore, this method will help students in giving meaning to their mastery in the learning process.